Resposta endometrial de jumentas (Equus asinus) da raça Pêga ao sêmen fresco, extendido e congelado de jumento - Toledo, Carmen Zilda Pereira de [UNESP] (2014)
The general objective of this study was to describe the inflammatory responses in Pêga Jennies from fresh (NM), extended (ES) and frozen (CS) semen from Jackass. The specific objective was to correlate these responses with low pregnancy rates in Jennies after artificial inseminations (AI) with frozen semen. Twenty five Jennies were daily evaluated by teasing, rectal examination and ultrasound from May 2002 to March 2013. Estrous cycles (n=234) were followed, with 33 (14.22%) non- ovulatory estrous and 11 (4.74%) double ovulations. The estrous cycle length was 32.68±0.76 days, with external heat signs of 4.49±0.23 days and time of ovulation in relationship to end of estrous of 5.68±7.18 hours for Jennies during the observed period. The estrous cycle was 28.88±0.95 days; with external heat signs of 4.50±0.35 days and time to ovulation in relation to end of estrous of 8.0±2.45 hours among 25 Jennies. Thus, considering the obtained results there was no reproductive seasonality. Twelve Jennies were casually selected for biopsy during diestrous being reproductively evaluated and subsequently submitted to one of those: natural mount (NM), AI- ES and AI-CS near the time of ovulations; and then submitted to endometrial biopsy 10 hours latter. Each fragment was maintained in formalin 10%, Bouin solution and Buffer glutaraldehyde 10% for Ligh Microscopy (LM), Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). The endometrial samples from Jennies in diestrous presented folds and endometrial grooves, microvillus cells and ciliated cells, free of process that could compromise reproduction. The estrous samples presented simple columnar epithelium, circled nuclei, condensed chromatin and at the cytoplasm, mitochondrial vacuoles and electro- dense corpuscles. Similar structures to blebs were present at the microvilli cell surface. The endometrial glands were completed by secretions that were shown with major evidence ...